E-Governance: The Implication of Next Social Generation Welfare Information System - Mulyana Abdul Aziz, Yaya; Ariesmansyah, Andre (Smart City, 2023)
Accelerating bureaucracy can be performed by e-governance present in order to improve the quality of government administration in the world. E-governance draft is closely related to the development of information and communication technology (ICT) globally. One form of embodiment of e-governance is the implementation of a smart city. smart cities are expected to be able to become a liaison between the demands of the community in appropriate, effective, and efficient services from the city government, by utilizing ICT. There are various related definitions of smart city in this world. One of them is as explained by Nam and Pardo who state "A smart city is a city that can identify various city problems ranging from social infrastructure to disasters. The results of the study that implementation E-Governance in the social welfare information system next generations The implementation is optimal and supportive if seen from the program, it is very good and in accordance with the vision and mission. However, there are still many obstacles related to unstable networks or server downtimes when proposing data as Integrated Social Welfare Data. Efforts must be made to integrate more with application users when proposing and verifying data so that it is valid and structured.